Changes in endogenous abscisic acid, trans-zeatin riboside, indole-3-acetic acid levels and the photosynthetic rate during the growth cycle of Curcuma alismatifolia gagnep. in different production seasons - P. Hongpakdee (2018)
Off-season (OS) cropping of Curcuma alismatifolia Gagnep. in Thailand results in a decline in plant growth and flowers quality compared to regular season (RS) cropping. This may be due to the distinct climatic conditions in OS such as short day length, lowtemperature, water stress etc. which induce changes in some endogenous hormones and alter plant growth and development. The experiments in two cropping season (RS and OS) were conducted to examine the changes to endogenous hormones i.e. abscisic acid, trans-zeatin riboside and indole-3-acetic acid, during the growth cycle. The result indicated that OS cropping brought about a decrease in plant height and flower quality but significantly stimulated the formation of rhizomes compare with RS cropping. The levels of ABA in leaves, old rhizomes and old storage roots were higher and consistently increased during off-season cropping. The maximum concentration of ABA was up to 2.2 μg gDW-1 in leaves, 1.4 μg gDW-1 in old rhizomes, 1.0 μg gDW-1 in old storage roots, 2.3 μg gDW-1 in inflorescence, 0.9 μg gDW-1 in new rhizomes, and 0.9 μg gDW-1 in new storage roots. The levels of ABA in RS cropping were relatively constant throughout growth stages and mostly less than 0.1 μg gDW-1. The levels of t-ZR were also slightly higher in leaves, old rhizomes, old storage roots, inflorescence and new rhizomes in OS than RS cropping. The increase of t-ZR in new rhizomes may cause the larger number of new rhizomes in OS cropping (4.8 per plant). The concentration of IAA in leaf exudates was similar between the two growth seasons except in the final stage. Therefore, it could be concluded that OS conditions induced a decrease in the photosynthetic rate, and increases in ABA and t-ZR concentrations in various organs at different growth stages, leading to depressed shoot growth and an increase in rhizome numbers. © Verlag Eugen Ulmer KG, Stuttgart.